Accuracy of the molecular diagnosis of duchenne and becker muscular dystrophy: A systematic review with meta-analysis - Fabian A. Chavez-Ecos; Carlos Quispe-Vicuña; Marco Malaga; Niels Pacheco-Barrios; Andrely Huerta-Rosario; Victor Velasquez-Rimachi; Peggy Martinez Esteban; Carlos Alva-Diaz (PLoS ONE, 2026)
Introduction Recently, Molecular diagnosis of Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) has become increasingly important in the management of these patients, with techniques such as multiplex ligation-dependent amplification (MLPA) and next-generation sequencing (NGS) coming to the fore. Therefore, this study aims to evaluate the diagnostic accuracy of MLPA, NGS, and the algorithm MLPA-NGS for confirmatory diagnosis of DMD/BMD. Methods We systematically searched databases (PubMed, Embase, Scopus, Cochrane and Web of Science) until July 2025 for studies evaluating the diagnostic accuracy of MLPA and/or NGS testing in patients with clinical suspicion of DMD, considering multiplex PCR or biopsy as the reference test. A meta-analysis was performed using a random-effects model to estimate the sensitivity, specificity, and detection rate of each test. The QUADAS-2 tool was used to assess the risk of bias and the GRADE criteria were used to identify the certainty of evidence. Results We included 10 studies (3786 patients) evaluating the use of MLPA and 14 studies (4333 patients) evaluating the use of NGS. For MLPA, the sensitivity was 0.80 (95%CI: 0.76–0.84; I 2 : 86%), the specificity was 0.93 (95%CI: 0.87–0.96; I 2 : 16%), and AUC 0.90 (CI-95%: 0.89–0.92). For NGS, the detection rate was 0.77 (95% CI: 0.61–0.87; I 2 : 94%). Furthermore, the detection rate increased to 0.97 (95% CI: 0.94–0.99; I 2 : 95%) when NGS was performed after MLPA. We observe a low risk of bias but with very low certainty in the estimations. Conclusions In patients with clinical suspicion of DMD, the MLPA test is very good but with very low certainty. However, in these patients with a negative MLPA, adding the NGS test would allow improve the detection rate. Therefore, the sequential use of these tests could be considered in patients who persist in the clinical suspicion.